Some Physiological Effect of Acacia Gum on Acute Renal Failure Induced by Gentamicin in Male Rabbits - Zainab A. H. AL-Mousawi; Ahlam A. AL-rikabi; Hind A. A. AL-Hamed (Institute of Medico-legal Publications Pvt Ltd, 2021)
Renal failure a case characterized by the impairment of the kidney to filter waste products from the body.The study aims to evaluate the potential effect of Acacia gum in the prevention of induced Acute renalfailure in the rabbit model. Eighteen healthy male domestic rabbits (Lepus cuniculus) were divided intothree groups. Group 1: normal rabbits as control, Group 2: animals were injected (70mg/kg. B.W) ofintramuscular gentamicin daily for 14 days for induction of acute renal failure, Group 3: animals weretreated with intramuscular injection (70mg/kg B.W) gentamicin daily and offered 15% Acacia gum withdrinking water for 14 days. At the end of the experiment Serum urea, uric acid, creatinine, blood ureanitrogen, calcium, sodium, and malondialdehyde were measured in addition to Urine analysis. The resultsshowed that the treatment of Acacia gum improved significantly serum uric acid, creatinine, urea, bloodurea nitrogen, electrolyte, and proteinuria. Also reduced malonaldehyde, urine Specific gravity, and pHlevels. Our findings conclude that GA can protect the kidney by enhancing antioxidant efficiency, and maybe useful in improving acute renal failure.